Post-synaptic Release of the Neuronal Tissue-Type Plasminogen Activator (tPA) - Lenoir, Sophie; Varangot, Alexandre; Lebouvier, Laurent; Galli, Thierry; Hommet, Yannick; Vivien, Denis (Frontiers in Cellular Neuroscience, 2019)
The neuronal serine protease tissue-type Plasminogen Activator (tPA) is an important player of the neuronal survival and of the synaptic plasticity. Thus, a better understanding the mechanisms regulating the neuronal trafficking of tPA is required to further understand how tPA can influence brain functions. Using confocal imaging including living cells and high-resolution cell imaging combined with an innovating labeling of tPA, we demonstrate that the neuronal tPA is contained in endosomal vesicles positives for Rabs and in exosomal vesicles positives for synaptobrevin-2 (VAMP2) in dendrites and axons. tPA-containing vesicles differ in their dynamics with the dendritic tPA containing-vesicles less mobile than the axonal tPA-containing vesicles, these laters displaying mainly a retrograde trafficking. Interestingly spontaneous exocytosis of tPA containing-vesicles occurs largely in dendrites.